The influence of the polyester substrate on the structure and performance of vacuum-deposited coatings - Howells, D; Henry, B; Assender, H; Médico, L; Leterrier, Y; Månson, J (2005)
This paper reports on an ongoing study of the microstructural, mechanical and gas barrier properties of plasma enhanced chemical vapor deposited (PECVD) SiOx coatings on PET [poly(ethylene terephthalate)], heat established (HS) PET, primer-coated HS PET and PEN [poly(ethylene naphthalate)] substrates. The deposited films are effective barriers to water vapor permeation, highly conformal and exhibit very few large scale defects. Variation in coating microstructure between the composites is observed by AFM. Internal stresses in the coatings are found to be compressive and low on all substrates. The substrate is found to influence some of the mechanical properties with the cohesive strength of the coating greatest for PEN and lowest on PET. In addition, a primer layer increases the adhesive strength between coating and substrate compared to plain PET and PEN. © 2005 Society of Vacuum Coaters.